Don't Get Lost in Translation: Integrating Developmental and Implementation Sciences to Accelerate Real-World Impact on Children's Development, Health, and Wellbeing - Wakschlag, Lauren S.; Finlay-Jones, Amy L.; MacNeill, Leigha A.; Kaat, Aaron J.; Brown, C. Hendricks; Davis, Matthew M.; Franklin, Patricia; Berkel, Cady; Krogh-Jespersen, Sheila; Smith, Justin D. (Frontiers in Public Health, 2022)
Translation of developmental science discoveries is impeded by numerous barriers at different stages of the research-to-practice pipeline. Actualization of the vast potential of the developmental sciences to improve children’s health and development in the real world is imperative but has not yet been fully realized. In this commentary, we argue that an integrated developmental-implementation sciences framework will result in a translational mindset essential for accelerating real world impact. We delineate key principles and methods of implementation science of salience to the developmental science audience, lay out a potential synthesis between implementation and developmental sciences, provide an illustration of the Mental Health, Earlier Partnership (MHE-P), and set actionable steps for realization. Blending these approaches along with wide-spread adoption of the translational mindset has transformative potential for population-level impact of developmental science discovery.